2022
DOI: 10.23917/khif.v8i1.15531
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Network and Support Vector Machine in Classification of Flower Images

Abstract: Flowers are among the raw materials in many industries including the pharmaceuticals and cosmetics. Manual classification of flowers requires expert judgment of a botanist and can be time consuming and inconsistent. The ability to classify flowers using computers and technology is the right solution to solve this problem. There are two algorithms that are popular in image classification, namely Convolutional Neural Network (CNN) and Support Vector Machine (SVM). CNN is one of deep neural network classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
0
9
0
2
Order By: Relevance
“…In Table 3, we can conclude that Opti-SA on the 4C flower dataset has the satisfactory performance, according to the result of accuracy, percision, recall, specificity and F1-score [49,52]. F1-score performs about 2% higher on 4C flower dataset than 3C flower dataset.…”
Section: ) Discussionmentioning
confidence: 89%
“…In Table 3, we can conclude that Opti-SA on the 4C flower dataset has the satisfactory performance, according to the result of accuracy, percision, recall, specificity and F1-score [49,52]. F1-score performs about 2% higher on 4C flower dataset than 3C flower dataset.…”
Section: ) Discussionmentioning
confidence: 89%
“…It is commonly used for regression and classification tasks but is particularly effective in classification problems 35 . Mawarni et al have shown the practical application of the SVM algorithm on external wound classification 36 . Wang et al also revealed that SVM could be effective in the classification of diabetic ulcers 37 .…”
Section: Discussionmentioning
confidence: 99%
“…CNN processing sequential model in python, while Faster R-CNN utilizes the framework from Tensorflow as framework of an open-source deep learning framework with a library to perform computational calculations with high performance [17]. The model is based on CNN [23], which acts as a backbone and produces an algorithm that can detect objects to perform classification quickly [24].…”
Section: Methodsmentioning
confidence: 99%